Pulmonary Artery Hypertension Associated with HIV Infection in Nine Year-Old Child - Baskoro Adi Prabowo; Abdus Samik Wahab; Hasanah Mumpuni (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Pulmonary arterial hypertension (PAH) is a serious life threatening and severe complication ofHIV infection. A PAH presentation in patient with HIV tends to non specific, result in recognizeddiagnosis at a later stage. A 9 year-old HIV patient came to Pediatric Clinic with a chief complaint of worsening dyspneu for 1 month, leg edema and difficulty lying on a flat bed. Patient showed signs and symptoms that lead to pulmonary hypertension. An ECG findings were sinus rhythm, right axis deviation, and right ventricular hypertrophy. Echocardiography findings showed rightventricular and atrial enlargement, and high probability of pulmonary hypertension. Blood examination showed CD 4 was 84 cells/μL. The patient was managed as pulmonary arteryhypertension associated with HIV (HIV-PAH) infection.The patient was admitted for 3 weeksand eventually discharged with relieve condition.